The Influence of Marketing Communication and Brand Image on Purchase Decisions at Indomaret Modern Retail Outlets in Bekasi - Aulia, Alda; Sari, Sukarni Novita; Juardi (Yayasan Sinergi Kawula Muda, 2025)
This research is motivated by the decline in the value of Indomaret's Top Brand Index which indicates that there are problems in marketing communication and brand image that have an impact on consumer purchase decisions, besides that there are problems in Indomaret's marketing communication that need special attention carried out through personal selling in outlets and also the frequency of salespeople in promoting loyalty programs is still lacking so that consumers are less attractive to join. This study aims to determine the influence of marketing communication and brand image on product purchase decisions at Indomaret's modern retail outlet in Bekasi. The research method used is descriptive quantitative using validity, reliability, classical assumption test, and multiple linear regression test. The study results showed that marketing communication and brand image positively and significantly affected purchase decisions, partially and simultaneously, with a contribution of 76.3% to the variation in consumer purchase decisions at Indomaret's modern retail outlet in Bekasi.